An Integration of "Online Interactive Apps" for Learning Application of Graph Theory to Enhance Creative Problem Solving of Mathematics Students - Wahyuningsih, Sapti; Satyananda, Darmawan; Qohar, Abd; Atan, Noor Azean (International Journal of Interactive Mobile Technologies (iJIM), 2020)
An Integration of “Online Interactive Apps” for learning can be a disruptive learning innovation in higher education. The material of the application of graph theory course has application topics in the real world. How students use the application can be used as a measure of creative problem solving. Mixed method was used in the study. The first phase of the study used one group non-randomized design pre-test and post-test. Participants were students who took courses in the application of graph theory. The second phase of the study involved an exploration of creative problem solving performance through qualitative interviews. Analysis of problem solving skills with creative problem solving instruments adapted from the CPS version 6. The average performance of students is very good in exploring data and building acceptance, performance is good in generating ideas and designing processes. Finding from this research is a significant improvement of students' Creative Problem-Solving by integrating learning the application of graph theory with “Online Interactive Apps”. The results obtained that 69% of student opinions  strongly agree on learning activity can improve creative problem solving. The implementation of “Online Interactive Apps” can be used as an alternative to disruptive learning innovation in mathematics teaching-learning.